Hubungan Antara Kepuasan Kerja Dengan Kinerja Perawat Dalam Ketepatan Pemberian Obat di Ruang Rawat Inap RS Baptis Batu - Yohana Maria Magdalena; Susilaningsih - -; Risna Yekti Mumpuni (Jurnal Keperawatan Muhammadiyah, 2020)
Administering medicine is one of the most common nursing procedures performed by nurses. Factors that can influence the accuracy of drug administration are organizational factors, unit management factors, and individual factors. These three factors influence the behavior of nurses in drug administration and will ultimately have an impact on patient safety outcomes. The success of nursing services is largely determined by the performance of the nurses themselves Job satisfaction is one aspect of the individual psychological factors themselves. Job satisfaction is needed for nurses to be able to improve the quality of health services. Nurses having positive job satisfaction will produce quality services. The purpose of this study is know whether there is a correlation between nurses' job satisfaction and the accuracy of drug administration in the inpatient room at the Baptist Hospital in Batu. This type of research is a correlational research design used is cross sectional design. The populations in this study were all inpatient nurses who fit the inclusion criteria as many as 32 nurses. The sampling technique used is total sampling techniques and data collection is done through a questionnaire and checklist by using the Lamda test data analysis method. The results of the Lamda test have a probability (sig) of 0.033. As the probability value is <0.05, the interpretation of the results Ho is rejected and H1 is accepted. So it can be concluded that there is a correlation between nurse job satisfaction and the accuracy of drug administration in the inpatient room at the Baptist Hospital in Batu. The suggestions of this research is that it is expected that hospitals can improve the welfare of employees so that the quality of nurses' performance can be obtained for the advancement of service to patients.